Analysis Of Service Quality To Passenger Satisfaction Using Gap Analysis And Importance Performance Analysis Methods In Bangsalae Crossing Port, Wajo District, South Sulawesi Province - Budi Mantoro; Dewi Kartika; Rahmat Hidayat (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
The Bangsalae Ferry Port is located in Siwa Village, Pitfeedua District, Wajo Regency, South Sulawesi Province. Bangsalae Ferry Port is a ferry port operated by the Transportation Service of Wajo Regency. The Bangsalae Ferry Terminal serves only one route, namely the Siwa - tobaku route. The Bangsalae Ferry Terminal has a very important role in improving the economy in Wajo Regency. Based on the survey results in the field, it was found that several services for passengers were not implemented properly, such as health facilities with inadequate equipment, absence of criminal prevention tools such as CCTV and audio speakers, clean water facilities in toilets / bathrooms, which were inadequate, no gangway facilities, information service facilities, parking attendants and luggage officers / porters do not use uniforms and there are no facilities for disabled / disabled passengers and space for breastfeeding mothers. In this study, the method used to analyze existing problems is the Customer Statisfaction Index, Gap Analysis and Importance Performance Analysis. Based on the analysis, it was found that the passenger satisfaction index was 72.98% with the highest gap in the equality dimension of - 0.92 and there were 9 service attributes in quadrant I that had to be improved and improved.